Snake Island in the Romanian and Ukrainian narrative in the International Court of Justice - Kastory, Agnieszka Małgorzata (Balcanica Posnaniensia. Acta et studia, 2024)
In 1948 Romania ceded Snake Island to the Soviet Union, which established a 12-mile maritime zone around the island. After the collapse of the USSR, the island was incorporated into Ukraine. Romania recognized that the island belonged to Ukraine, but a long-running dispute began between Ukraine and Romania over the delimitation of the shelf and the exclusive economic zone. Snake Island became part of this dispute because Ukraine considered it a reference point for the delimitation of the maritime waters. Romania strongly disagreed and referred the dispute to the International Court of Justice in The Hague. Both countries presented their arguments not only from the legal, but also historical point of view. They drew completely different conclusions from the same historical sources while presenting their interpretations of the past regarding Snake Island. The dispute ended when the ICJ announced its verdict on February 3, 2009. Both countries accepted it.